UV-LED lithography system using programmable light and tilt-rotational stage for 2D/3D microfabrication for micromachined RF devices - Shiba, Sabera Fahmida (Kansas State University, 2022)
In this dissertation, computer-controlled multidirectional UV-LED (Ultra-Violet Light Emitting Diode) lithography has been investigated for microscale three-dimensional (3-D) fabrication processes. The scalability, changeable light intensity, and multidirectional exposure capabilities of an array of UV-LEDs as a UV light source were described and investigated for the fabrication of both conventional semiconductor devices and advanced MEMS (Micro-Electro-Mechanical-Systems) devices. The UV-LED beam is diverging in nature and fades within a short distance. Therefore, commercial collimating equipment, like Fly’s eye integrator is not suitable for the UV-LEDs. The primary contribution of this research is the development of a single lens collimation scheme for making a collimated UV-LED light source. A significant advantage of this scheme is that a high enough intensity is preserved even after collimation, facilitating millimeter-tall microfabrication. In the process of collimating the UV-LEDs individually, high contrast is observed, which is later compensated using a continuous rotation of the light source. Utilizing the independent control and the behavior of LED with the change of current and distance, additional features like regional control and adjustable intensities were added to the system. The integration of a tilt-rotational sample holder introduces the opportunity to create 3D traces of the light on the target sample, which is unique among lithography systems. In addition, the adjustable intensities remunerate the non-uniformity of the intensity caused by the inclination of the sample. The light source combines 365 nm (i-line) and 405 nm (h-line), where the i-line spectrum is targeted for several hundred-micrometer tall microfabrication, and the h-line is targeted for millimeter tall microfabrication. With the functional scalability, a large-scale (8 inch²) light source has been demonstrated with two different optical designs, one using commercial Cabochons (Pandahall) as lenses and the other with customized hexagonal lenses. The lithography system achieved collimation with a deviation of 4.13˚ with the commercial lens and a deviation of 3˚ with the hexagonal lens. An intensity of 472 mW/cm² and 258 mW/cm² were obtained from the H-line and I-line UV-LEDs respectively which is the highest so far. The high contrast of around 34% caused by the UV-LED matrix was minimized to around 2.5% by utilizing an orbital rotation of the LED arrays. The light source has been characterized for 8.5% uniformity. The 2D structures with a resolution of 1.4 µm and the 3D vertical structures with a height of 3.14 mm have been demonstrated using different light profiles. Complex 3D microstructures like a flat bowtie, horn, bipod, tripod, open bowtie, double arrow, three-petalled flowers, and wind vanes were fabricated utilizing the programmable multidirectional functions. A future direction of the research has been demonstrated where a self-tiltable UV-LED light source was built with an inclination range of +70˚ to -70˚. This design helps eliminate the non-uniform exposure over an inclined sample and introduces a time-efficient complex 3D microfabrication method for liquid photoresists. An array of ultra-tall microstructure fabricated using the UV-LED lithography system showed the successful application as RF frequency-selective device in the 5G frequency range. Since the RF devices are strictly responsive to their parameters, a height of around several millimeters is needed for 5G device fabrication. The high intensity of the system was able to fabricate around 2.7 mm vertical pillars resonating to 27.8 GHz. This lithography system can replace conventional UV lamps with higher and adjustable intensity ranges, larger exposure areas, multidirectional exposure, and user-friendly automatic lithography operations. In addition to tall and versatile 3D microfabrication, this system gives superior surface quality and higher production yield compared to similar technologies. With the versatile functionalities and demonstrated capabilities, this lithography tool has potential uses in bioMEMS, RF MEMS, sensors, and many other major semiconductor and MEMS applications.
Keywords: Lithography; 3D microfabrication; RF MEMS; Programmable multidirectional lithography; UV-LED light source; 5G frequency selective device